Education in post-classical era - Nina V. Nalivayko (Moscow Polytechnic University, 2022)
The review takes up the key issues elaborated in the monograph "Educational Institution, Power and Society in the Age of Knowledge Culture Growth" (A.O. Karpov). These key issues include: the leading role of research education in the process of the new technological setup formation; processes of knowledge culture deconstruction and the policy of education commodification, in particular; the fundamentals of cognitive and cultural polymorphism of educational systems, well-grounded by the analysis of ethno-diversification models and socio-cognitive specific features typical for the society of knowledge; paradigmatically differentiated structure of modern education. Special mention of the high significance of the material presented in the text of the monograph has been made.